A retrospective analysis of the treatment results of 1557 patients with acute cholecystitis - Kirkil, Cuneyt; Bulbuller, Nurullah; Ilhan, Yavuz Selim; Aygen, Erhan; Gulturk, Baris; Coskun, Serdar (Pakistan Medical Assoc, 2015)
Objective: To analyse outcomes of variable management strategies for the treatment of Acute Cholecystitis in relation to morbidity, mortality and conversion to open surgery. Methods: The retrospective study was conducted at Firat University Hospital, Turkey and comprised records of Acute Cholecystitis patients admitted between 2005 and 2011. Patients were divided into subgroups according to admission time as well as American Society of Anaesthesiologists score. The outcomes of early cholecystectomy, interval cholecystectomy, delayed cholecystectomy, 'cooling-off' therapy and percutaneous cholecystostomy were evaluated. Mortality, morbidity, and conversion to open surgery were calculated as measures of success. Data was analysed using SPSS. Results: Of the 1557 patients, 1052(67.6%) were female. The overall mean age was 42.4+/-14.7 years. Success rates of 'cooling-off' therapy and percutaneous cholecystostomy were 89.3% and 96.3%, respectively. The conversion rate following delayed cholecystectomy was 30%, which was higher than that of both early and interval cholecystectomy (0.2% and 0%, respectively; p<0.001 each). Mortality and morbidity rates of delayed cholecystectomy (57.1% and 7.1%, respectively) were also significantly higher than early and interval cholecystectomy (5% and 0.1%; 5.6 and 0%, respectively). Conclusion: Early laparoscopic cholecystectomy and interval cholecystectomy shared similar outcomes and rates of efficacy. Percutaneous cholecystostomy was a successful treatment option for high-risk patients, while delayed cholecystostomy correlated to the highest rates of conversion to open surgery, mortality and morbidity.
Keywords: Cholecystitis; Laparoscopic; Cholecystostomy